Harga Pokok Produksi dengan Metode Full Costing pada UMKM 4K Canteen & Kost - Riyanto, Muhamad; Daffa, Muhammad Ammar; Ramadhan, Rama; Rahma, Amelia; Arifin, Qoria Keisyarani (Value : Journal of Management and Business, 2024)
This research aims to gain an understanding of the calculation of the cost of goods manufactured using the Full Costing method. In addition, this research also looks for differences when calculating the cost of goods produced from 4K Cost & Canteen MSMEs. After the research was conducted, it revealed the details of each cost that had been incurred by 4K Cost & Canteen using the Full Costing method. It was found that there were differences in calculations with these MSMEs. The MSME's cost of goods produced for chicken pieces was IDR 2,802,000, and the cost of goods produced for drinks was IDR 2,625,000. After the research was carried out using the Full Costing calculation method, the cost of goods such as chicken pieces amounted to IDR 3,452,500, and the cost of production of Hoola drinks amounted to IDR 3,168,000, when compared to the calculation using the Full Costing calculation method. from the research that has been done that there are costs that have not previously been calculated by 4K Kost & Canteen during the production period.